UNRAVELING THE LINK BETWEEN TRAIT MINDFULNESS AND FRIENDSHIP DYNAMICS: THE MEDIATING POWER OF EMPATHY AND SOCIAL RESPONSIVENESS - Palwasha Nasir Abbasi; Bakhtawar Saeed; Iffat Nishat (Policy Research Journal, 2025)
Trait mindfulness is linked to interpersonal connections of a person including the dynamics of friendship. The present study is aimed to find out the association between trait mindfulness and dynamics of friendship and the mediating function of social responsiveness and empathy between the two variables. The sample comprises of three hundred adults from various regions of Pakistan. The measures utilized in the study incorporates Mindfulness Attention Awareness Scale (MAAS), Friendship Dynamics Scale (FDS), Perth Empathy Scale (PES) and Brief Social Responsiveness Scale (SRS). Results indicated that substantial positive association is found between trait mindfulness and dynamics of friendship whereas positive empathy (both cognitive and affective) mediates the association between trait mindfulness and dynamics of friendship. The negative empathy (cognitive and affective) does not have potential mediating role. Furthermore, social responsiveness mediates the path between the two variables. In a nutshell, when the trait mindfulness increases, the cognitive and affective empathy and social responsiveness also increases which eventually fosters the interpersonal interactions.